GAYA KEPEMIMPINAN, KEMAMPUAN DAN LINGKUNGAN KERJA PENGARUHNYA TERHADAP KOMITMEN KERJA KARYAWAN OPERASIONAL PADA PT. QUANTUM SARANA MEDIK DENPASAR - Ida Bagus Gede Udiyana; Putu Kepramareni; Luh Febriani (Faculty of Economics and Business, Universitas Warmadewa, 2018)
Commitment to the organization is an event where people are very interested and have the attachment to the goals, values and goals of the organization. The commitment includes a very favorable attitude organization always oriented attitude and strong drive to seek a high level of effort for the benefit of the organization for the smooth achievement of organizational goals. The purpose of this study was to analyze the effect of simultaneously between Leadership Style, Capability and Work Environment for Employees' Commitment Operations PT. Quantum Sarana Medik Denpasar. Data used in this research is quantitative data and qualitative data, the data source is primary data. Data collection method used is the method of observation, interviews and questionnaires with sensus. Techniques of analysis is Classical Assumption Test, Regression and Hypothesis Testing. The results simultaneously linear regression analysis showed that the style of leadership, ability and work environment and a positive effect significantly to the operational employee commitment. PT. Quantum Sarana Medik Denpasar. This is evident from the results of test calculations show that Fhitung 14.859 F larger than F table 0.000 significance level of 3.24 and less than 0.05 with a coefficient of determination (R2) of 0.686, this means that the influence of all independent variables on the dependent variable includes commitments employment by 68.6% and the remaining 31.4% is explained by other variables not examined. The most dominant influence on employee commitment is a style of leadership that is equal to 0,556. Advice given is the leader should further develop its leadership style towards subordinates. This would include making communications with employees in accordance with the maturity level employees so that employees can understand the message delivered by the leader and avoid misunderstandings. Keywords: leadership style, ability, work environment and work commitments